A healthy context, a just context? The role of classroom-level victimization in the adverse effects of bullying victimization on students' belief in a just world - Graf, Daniel; Yanagida, Takuya; Laninga-Wijnen, Lydia; Garandeau F., Claire; Salmivalli, Christina (Elsevier, 2025)
The phenomenon that victims of bullying experience greater psychological problems in environments with lower levels of victimization is known as the healthy context paradox. The current study investigated the healthy context paradox with respect to students' belief in a just world. Specifically, we examined prospective effects of bullying victimization on personal and general belief in a just world, while taking the classroom level of victimization into account. Based on self-reports from 2010 Finnish 4th to 9th grade students (50.9 % girls, Mage = 12.6, SD = 1.71), multilevel models revealed negative prospective associations between bullying victimization and both types of belief in a just world. In addition, classrooms with initially lower levels of victimization subsequently showed higher levels in both types of belief in a just world. Finally, the adverse effects of bullying victimization on both types of belief in a just world were stronger in classrooms with lower levels of victimization. Our results support and extend the healthy context paradox. Implications, particularly for prevention and intervention strategies are discussed.